Agricultural Legislation: The Presence of California Proposition 2 on YouTube - Joy Goodwin; Emily Rhoades (Journal of Applied Communications, 2011)
Animal rights movements continue to be a threat to the livestock industry in the United States. In 2008 California voters passed a proposition (2) which outlawed the use of battery cages for laying hens, gestation crates for sows, and veal crates for veal calves by 2015. Similar measures have previously been passed in Florida, Arizona, Colorado, and Oregon. As animal rights activists continue to pressure the livestock industry, it is important to look at their information outlets, especially those targeted toward young voters. The researchers used content analysis to determine the message content and campaign for Proposition 2 posted on YouTube. By using the search term “proposition 2 California,” a usable sample of 103 videos were identified. Results indicate that when dealing with political legislation, agriculture has very little web presence on YouTube. In addition, it indicates that those in favor of the proposition use appeals and biased examples to deliver their message. In order to be relevant to young voters, agriculture advocates must begin using technology to reach non-agriculture audiences. Educators must also be preparing future communicators to embrace such technology in campaigns.
Keywords: Animal rights acctivists; proposition 2 on YouTub; non-agriculture.